TRAINING IN OPERATING MICROSOFT WORD AND MICROSOFT EXCEL COMPUTERS IN CHILDREN IN KLAMPOKAN SITUBONDO VILLAGE - Yesi Puspitasari; Irma Noervadila; Firman Jaya (STKIP PGRI SITUBONDO, 2022)
A computer is an electronic device that is used to calculate. The development of computer technology metamorphosed into internet technology where the internet has become an important part of the various application used for business, including information system applications. The development of the internet has penetrated almost all corners of the world, including one of them, namely Klampokan Village in Panji District, Situbondo regency. Microsoft Word dan Microsoft Excel is software that must be mastered by children from now on. The problem is that computer facilities and rooms are in the village hall, but the lack of knowledge about the use of Microsoft Word and Excel applications and the lack of teaching media in schools such as teachers and computers and the absence of computer training lessons in Klampokan Village, especially Microsoft Word and Excel are the reasons for the children in Klampokan Village. Panji District cannot use Microsoft Word and Excel. The existence of Microsoft Word and Microsoft Excel computer operation training is so that the Klampokan village children master the techniques of making financial reports, making tables, and financial report headers, including writing the correct formula format, logic truth, table format, and in the future being able to help the Klampokan Village administration.